Social Media Usage Pattern and Its Impact on Academic Performance of Public-Sector Medical Students - Hafiz Muhammad Ahtisam Idrees; Fariha Salman; Rozina Shahadat Khan; Arshia Mansha; Musfira Habib; Muhammad Shoaib; Risha Naeem (Proceedings, 2025)
Introduction: Social media plays a vital role in students' lives, providing connectivity and access to information while posing distraction risks.